Study on Modified Dynamic Constitutive Model for Calcareous Sand considering Particle Breakage. (26th April 2022) - Chen, Huibin; Hou, Heying; Jiang, Pengming; Nong, Zhenzhen; Li, Tianxiang; Wang, Qing; Pan, Zhuojie
Abstract : Calcareous sand is special sand widely distributed in the South China Sea, which is characterized by the irregular particle shape, high porosity, easy-breaking, etc. Through a series of dynamic triaxial tests, this paper will study the influence of particle breakage on the dynamic deformation characteristics of calcareous sand and explore a modified dynamic constitutive model considering particle breakage suitable for calcareous sand. The research shows that the dynamic deformation characteristics of calcareous sand can be described by the Hardin-Drnevich model. The maximum dynamic shear modulus and average effective stress of calcareous sand obey Janbu empirical formula, with approximate a linear relationship. Through screening experiment, it is found that there is a linear relationship between particle crushing rate and effective confining pressure. On the basis of Hardin-Drnevich, the dynamic constitutive model of calcareous sand considering the influence of particle breakage is established by introducing relative crushing rate Br and constitutive model parameters. By comparing with the experimental data, it is found that the relative error between the calculated value and the experimental value of the model is no more than 12%, and the average error is no more than 8%, indicating that the modified dynamic constitutive model can better predict the dynamic characteristics of calcareous sand.